KRITIK SOSIAL DALAM PUISI “DIPONEGORO” KARYA CHAIRIL ANWAR: MENELUSURI PERLAWANAN TERHADAP KETIDAKADILAN SOSIAL - Handiansyah, Dandi; Zai, Mega Susanti; Yunus, Syarifudin (Cahaya Ilmu Bangsa Institute, 2025)
This study aims to reveal the form of social criticism in the poem “Diponegoro” by Chairil Anwar using stylistic and sociological literary approaches. Chairil Anwar, a prominent figure of the '45 Generation, is known for his revolutionary works that voice resistance against injustice. In this poem, Chairil resurrects the figure of Prince Diponegoro as a symbol of struggle and perseverance in the face of oppression. The study employs a qualitative descriptive method with content analysis techniques to examine the poem’s diction, figurative language, symbols, and meanings, as well as its connection to the socio-political context of post-independence Indonesia. The analysis reveals that “Diponegoro” is not only a tribute to a national hero but also rich in social criticism towards the decline of revolutionary ideals in the post-independence era. The linguistic elements such as repetition, metaphor, and heroic imagery demonstrate the poem’s expressive power in awakening readers' awareness and spirit. The poem serves as both a medium of cultural resistance and a call to continue fighting against new forms of oppression during the development era. Thus, Chairil Anwar's work proves to hold strong social relevance and reflects the realities of his time through literary aesthetics.